Isolation, Classification and Antagonistic Properties of Alkalitolerant Actinobacteria from Algerian Saharan Soils. Issue 9 (1st September 2020) - Meklat, Atika; Bouras, Noureddine; Mokrane, Salim; Zitouni, Abdelghani; Djemouai, Nadjette; Klenk, Hans-Peter; Sabaou, Nasserdine; Mathieu, Florence
Abstract: The Sahara, one of the most extreme environments on Earth, constitutes an unexplored source of alkalitolerant actinobacteria. In this work, we studied the diversity of alkalitolerant actinobacteria in various soils collected from different regions of the Algerian Sahara. A total of 29 alkalitolerant actinobacterial strains were isolated by using a complex agar medium. The diversity of these actinobacteria was evaluated using a polyphasic approach, which included morphological, chemotaxonomic, physiological (numerical taxonomy) and 16S rRNA gene analyses. The isolates which were assigned to the genus Nocardiopsis, shared relatively low 16S rRNA gene sequences similarities compared to closely related species suggesting that they belonged to putatively new species. All of the strains were tested for antibiotic activity against a broad range of microorganisms and screened for genes encoding polyketide synthases and non-ribosomal peptide synthetases and found to have the potential to produce secondary metabolites. Consequently, the study supports the view that extreme environments contain many novel actinobacteria, which represent an unexplored source for the discovery of biologically active compounds.